De Juanjo a Millás en El mundo - Fontalba Espejo, Ana Pilar (Universidad Nacional del Litoral, 2018)
This paper aims to provide a critical and interpretative analysis about Juan José Millás’ novel El mundo (2010) as an autofictional text, which emphasizes the formal and thematic link between autofiction and childhood narrative.